Motivational Interviewing as a Tool to Increase Motivation and Adherence to a Long COVID Telerehabilitation Intervention: Secondary Data Analysis from a Randomized Clinical Trial - León-Herrera S; Oliván-Blázquez B; Samper-Pardo M; Aguilar-Latorre A; Sánchez Arizcuren R (Psychology Research and Behavior Management, 2024)
Sandra León-Herrera,1,2 Bárbara Oliván-Blázquez,1,2 Mario Samper-Pardo,3 Alejandra Aguilar-Latorre,1,2 Rafael Sánchez Arizcuren4 1Institute for Health Research Aragón (IIS Aragón), Zaragoza, Spain; 2Department of Psychology and Sociology, University of Zaragoza, Zaragoza, Spain; 3Department of Health Sciences, University of Zaragoza, Zaragoza, Spain; 4Department of Physiatry and Nursing, University of Zaragoza, Zaragoza, SpainCorrespondence: Bárbara Oliván-Blázquez, C. Violante de Hungría, 23, Zaragoza, 50009, Spain, Tel +34 622719759, Email bolivan@unizar.esBackground: Although motivational interviewing was originally developed to address abuse disorders, scientific evidence confirms that it is an increasingly used and effective approach in a wide range of therapeutic interventions. To date, however, no studies have analyzed the use of this tool in patients with persistent symptoms following coronavirus disease 2019, a condition known as Long COVID.Purpose: To analyze the effectiveness of motivational interviewing with regard to the adherence to telerehabilitation for Long COVID using a mobile application. As a secondary objective, factors related to greater motivation before and after the motivational interviewing techniques were analyzed.Patients and Methods: This longitudinal design substudy used a sample of 52 adult patients with Long COVID participating in the intervention group of a randomized clinical trial. This trial examined the effectiveness of a telerehabilitation program for this population using a mobile application. This program included three motivational interviews to achieve maximum treatment adherence. In this study, the main variables were motivation and adherence to application use. Sociodemographic and clinical data, personal constructs, and affective state were also collected. Subsequently, a descriptive, correlational, and regression statistical analysis was performed using the SPSS Statistics program.Results: The median motivation prior to the first motivational interview was 8 (IQR 2), the median at the end of the last motivational interview was 8.5 (IQR 2.75), and the change in motivation levels after the three motivational interviews was 0.5 (IQR 1). Affective state and final motivation scores were predictors of greater adherence to telerehabilitation treatment.Conclusion: A high level of motivation after participating in motivational interviewing appears to be related to higher levels of adherence to telerehabilitation in patients with Long COVID. This suggests that motivational interviewing may be an effective tool in the treatment of this disease.Keywords: motivational interviewing, Long COVID, telerehabilitation, motivation, personal constructs, affective state